Neural correlates of attention‐executive dysfunction in lewy body dementia and Alzheimer's disease. Issue 3 (26th December 2015) - Firbank, Michael; Kobeleva, Xenia; Cherry, George; Killen, Alison; Gallagher, Peter; Burn, David J.; Thomas, Alan J.; O'Brien, John T.; Taylor, John‐Paul
Abstract: Attentional and executive dysfunction contribute to cognitive impairment in both Lewy body dementia and Alzheimer's disease. Using functional MRI, we examined the neural correlates of three components of attention (alerting, orienting, and executive/conflict function) in 23 patients with Alzheimer's disease, 32 patients with Lewy body dementia (19 with dementia with Lewy bodies and 13 with Parkinson's disease with dementia), and 23 healthy controls using a modified Attention Network Test. Although the functional MRI demonstrated a similar fronto‐parieto‐occipital network activation in all groups, Alzheimer's disease and Lewy body dementia patients had greater activation of this network for incongruent and more difficult trials, which were also accompanied by slower reaction times. There was no recruitment of additional brain regions or, conversely, regional deficits in brain activation. The default mode network, however, displayed diverging activity patterns in the dementia groups. The Alzheimer's disease group had limited task related deactivations of the default mode network, whereas patients with Lewy body dementia showed heightened deactivation to all trials, which might be an attempt to allocate neural resources to impaired attentional networks. We posit that, despite a common endpoint of attention‐executive disturbances in both dementias, the pathophysiological basis of these is very different between these diseases. Hum Brain Mapp 37:1254–1270, 2016 . © 2015 The Authors Human Brain Mapping Published by Wiley Periodicals, Inc .